Mode I stress intensity factor for a cracked plate with an integrated piezoelectric actuator - Abuzaid, Ahmed; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (Trans Tech Publications, Switzerland, 2015)
The fracture performance of cracked structures is dominated by singular stress in the crack tip vicinity. In fracture mechanics, most interest is focussed on stress intensity factors, which describe the singular stress field ahead of a crack tip and govern fracture of structures when a critical stress intensity factor is reached. In the present work, linear fracture mechanics is applied in order to obtain the fracture toughness parameters of a cracked plate integrated with piezoelectric actuator under mode I loading. An analytical model was derived to represent the relation between piezoelectric parameters and stress intensity factor and energy release rate. The results indicate that the stress intensity factor decreases linearly with the application of the different piezoelectric actuator voltages.